2018
DOI: 10.21037/atm.2018.05.52
|View full text |Cite
|
Sign up to set email alerts
|

The role of epithelial growth factors and insulin growth factors in the adrenal neoplasms

Abstract: Human fetal and adult adrenal gland express both insulin growth factor-1 (IGF-1) and IGF-2, their receptors (IGF-Rs) and a variety of specific IGF binding proteins suggesting their potential role in the regulation of adrenal growth and function. overexpression is essential for the growth of monoclonal lesions, such as large benign adenomas (ACA) and adrenocortical carcinomas (ACC) and has been found to contribute to tumorigenesis in Beckwith-Wiedemann syndrome. IGF-2 is the most highly expressed gene observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 82 publications
0
13
0
1
Order By: Relevance
“…In humans, fetal and adult adrenal gland has been shown to express insulin-like growth factor 1/2 (IGF-1/2) and its receptors, and these play a role in the growth and function of the adrenal gland. It has also been suggested that IGF-2 overexpression may cause benign adenomas and adrenocortical carcinomas (11). Hyperinsulinemia resulting from IR is reported to increase IGF-1 and IGF-1 receptors at the same time, by increasing IGF-1 and IGF-2 levels.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, fetal and adult adrenal gland has been shown to express insulin-like growth factor 1/2 (IGF-1/2) and its receptors, and these play a role in the growth and function of the adrenal gland. It has also been suggested that IGF-2 overexpression may cause benign adenomas and adrenocortical carcinomas (11). Hyperinsulinemia resulting from IR is reported to increase IGF-1 and IGF-1 receptors at the same time, by increasing IGF-1 and IGF-2 levels.…”
Section: Discussionmentioning
confidence: 99%
“…The IGF-2 gene is located at 11p15 region that consists of a telomeric domain including the IGF-2 and H19 that might modulate IGF-2 expression and a centromeric domain including cyclin dependent kinase inhibitor (CDKNIC) involved in the G1/S phase of the cell cycle [ 11 ]. IGF-2 gene encodes IGF-2 protein and it is expressed by both fetal and adult adrenal glands and as a part of complex signaling system which plays an important role in normal growth and development, cell survival and proliferation as well as in malignant alteration [ 15 ]. IGF-2 overexpression was proven in more than 85% of ACCs although it is low or absent at the beginning of clonal proliferation [ 16 ].…”
Section: Pathogenesis Of Adrenocortical Cancermentioning
confidence: 99%
“…Despite of its rarity, with global prevalence of 4–12 cases per million, adrenocortical carcinoma is the second, after anaplastic thyroid carcinoma, most lethal endocrine malignancy with 5-year overall survival being < 15% in advanced ACC [ 15 , 42 , 198 ]. The main obstacle is scarcity of effective and available treatment options [ 27 ].…”
Section: Treatment Optionsmentioning
confidence: 99%
“…These drugs potentially inhibit a cascade of signaling events that regulate cell growth and angiogenesis. Overexpression of tyrosine kinase receptors was documented in ACC particularly vascular endothelial growth factors and receptors (VEGF/VEGFR), epidermal growth factor and receptor (EGF/EGFR) and insulin-like growth factor (IGF) system comprised by the IGF ligands (IGF-1, IGF-2, insulin) and their cell surface receptors (IGF-1R, IGF-2R and insulin receptor) [23][24][25].…”
Section: Molecular Rationalementioning
confidence: 99%
“…Signaling pathways such as PI3K/AKT/mTOR and MAPK (Ras/ Raf/MEK/ERK) resulting in cell survival, proliferation and tumor growth, are activated through IGF-1R and EGF-R in ACC [25].…”
Section: Molecular Rationalementioning
confidence: 99%